The Walking Concepts: Zombie Categories in Communication Theories - Scolari, Carlos A. (Estudios sobre el Mensaje Periodístico, 2026)
This article offers a critical reflection on the life cycle of concepts in the social sciences and communication theories. It focuses on the figure of the ‘zombie concept,’ understood as an analytical category that, despite having lost its explanatory power, continues to circulate in academic discourse. Drawing on the interventions of scholars such as Ulrich Beck, Elihu Katz, Klaus Krippendorff, Bruno Latour, and Eliseo Verón, the text also examines how certain concepts -from neoliberalism to imperialism- become nominalized forms that simplify the understanding of ongoing processes and operate as single-cause explanations. The problem is not ontological but discursive: the ritualized and uncritical use of many concepts produces theoretical blindness and impoverishes scientific understanding. In response to this drift, the article advocates a reflexive practice aimed at revising, retiring, or revitalizing concepts to reopen debate and renew the vocabulary of the social sciences and communication theories.
Keywords: Communication theories; epistemology; zombie concepts; nominalized forms